2016
DOI: 10.1142/s1793830916500439
|View full text |Cite
|
Sign up to set email alerts
|

On the complement of a graph associated with the set of all nonzero annihilating ideals of a commutative ring

Abstract: The rings considered in this paper are commutative with identity which are not integral domains. Recall that an ideal [Formula: see text] of a ring [Formula: see text] is called an annihilating ideal if there exists [Formula: see text] such that [Formula: see text]. As in [M. Behboodi and Z. Rakeei, The annihilating-ideal graph of commutative rings I, J. Algebra Appl. 10(4) (2011) 727–739], for any ring [Formula: see text], we denote by [Formula: see text] the set of all annihilating ideals of [Formula: see te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Hence, ra ∈ I ⊆ A. This proves that A is an ideal of R. Similarly, it can be shown that B is an ideal of R. Now, it can be shown as in the proof of (i) ⇒ (ii) of ( [19], Proposition 2.10) that both A and B are maximal N-primes of (0) in R and A ∩ B = (0). It is now clear that R is a reduced ring and {A, B} is the set of all minimal prime ideals of R. Proof.…”
Section: Note That a Is Of The Formmentioning
confidence: 57%
See 4 more Smart Citations
“…Hence, ra ∈ I ⊆ A. This proves that A is an ideal of R. Similarly, it can be shown that B is an ideal of R. Now, it can be shown as in the proof of (i) ⇒ (ii) of ( [19], Proposition 2.10) that both A and B are maximal N-primes of (0) in R and A ∩ B = (0). It is now clear that R is a reduced ring and {A, B} is the set of all minimal prime ideals of R. Proof.…”
Section: Note That a Is Of The Formmentioning
confidence: 57%
“…We know from Lemma 8 that H = (Ω(R)) c . Hence, (Ω(R)) c is star and so, we obtain from (i) ⇒ (ii) of ( [19], Proposition 2.12) that R ∼ = D × F as rings, where F is a field and D is an integral domain but not a field. (ii) ⇒ (i) Let us denote D × F by T , where F is a field and D is an integral domain but not a field.…”
Section: Note That a Is Of The Formmentioning
confidence: 86%
See 3 more Smart Citations